Highly Flexible and Twistable Freestanding Single Crystalline Magnetite Film with Robust Magnetism. (28th May 2020) - An, Feng; Qu, Ke; Zhong, Gaokuo; Dong, Yongqi; Ming, Wenjie; Zi, Mengfei; Liu, Zhijie; Wang, Yadong; Qi, Biyun; Ding, Zhen; Xu, Jun; Luo, Zhenlin; et al.
Abstract: Magnetic materials and devices that can be folded and twisted without sacrificing their functional properties are highly desirable for flexible electronic applications in wearable products and implantable systems. In this work, a high‐quality single crystalline freestanding Fe3 O4 thin film with strong magnetism has been synthesized by pulsed laser deposition using a water‐dissolvable Sr3 Al2 O6 sacrificial layer, and the resulting freestanding film, with magnetism confirmed at multiple length scales, is highly flexible with a bending radius as small as 7.18 µm and twist angle as large as 122°, in sharp contrast with bulk magnetite that is quite brittle. When transferred to a polydimethylsiloxane support layer, the Fe3 O4 film can be bent with large deformation without affecting its magnetization, demonstrating its robust magnetism. The work thus offers a viable solution for flexible magnetic materials that can be utilized in a range of applications. Abstract : A high‐quality single crystalline freestanding Fe3 O4 thin film with strong magnetism has been synthesized by pulsed laser deposition using water‐dissolvable Sr3 Al2 O6 sacrificial layer, and the resulting freestanding film is highly flexible. When transferred to the polydimethylsiloxane support layer, the Fe3 O4 film can be bent with large deformation without affecting its magnetization, demonstrating its robust magnetism.